THE IDEA OF SOCIAL HARMONIZATION IN THE WORKS BY MYKOLA HOHOL - Голянич, М. Ю. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
On the basis of the analysis of works by Mykola Hohol the article highlights his approach to understanding of the ‘a human being – society’ correlation. The article deals with the central Hohol’s idea of that of the social relationship harmonization by means of ‘the human’s revival’. The author’s Ukraine-oriented thinking as well as his vivid expression of the idea of Ukraine is underlined.